PENGGUNAAN WOOD PELLET UNTUK BAHAN BAKAR PRODUKSI TAHU DI UKM KAB. KEDIRI - Eko Yohanes Setyawan; Abraham Lomi; Choirul Saleh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi Nasional Malang, 2021)
Wood pellet is an alternative fuel made from wood waste, is one of the renewable fuels that is environmentally friendly, has a cylindrical shape and is hard, this is one of the energy conversions where the process of changing the energy form of wood waste which is randomly sized is converted into a cylindrical pellet form. This service is carried out to determine the impact of rising fuel prices on the pattern of fuel use in the tofu production process in Kab. Therefore, it is necessary to analyze the efficiency of the system analyzed, namely the efficiency of the combustion system in the production of tofu. What is known is the direct energy input in each soybean cooking process and the pattern of energy use in tofu production. From the analysis that has been done to get wood pellet fuel to get maximum results for soybean cooking in a burning time for 1 hour it takes 1/2 kg of wood pellets, if done one day by burning for 8 hours in the soybean porridge cooking process it takes 4 wood pellets kg.